Survei Tingkat Pemahaman Mahasiswa Mengenai Ancaman Keamanan Sistem pada Facebook - Eddy Ryansyah; Muhamad Yoga Fauzan; Reymen Maulana; Chaerur Rozikin (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
Facebook is an example of a platform of social media and has become one of the best-selling media in Indonesia and even in the world. It may be said one person in the world has one facebook account. The platform is used as a forum for users to interact with friends, relations, colleagues, and even families outside the city. This social media application provides many facilities as follows, sharing statuses, in the form of texts, images, and videos. In this research, the researcher explores the theme of threats on facebook including phishing, link scam, and clickjacking. The researcher also analyzes the causes, how the lurking threats work and how to deal with or prevent them. The research uses a quantitative approach. The data collection method is carried out using a survey and a library research. The samples collected in the research are 58 respondents who are all students having used Facebook. Based on the research results, the researchers conclude that most respondents do not understand or even know the various system security threats on Facebook.